DEVELOPMENT OF A WEB-BASED CYBER COUNSELING MODEL FOR GUIDANCE AND COUNSELING SERVICES AT SMA NEGERI 1 BAYUNG LENCIR - HANAPI, KHOIRUL; Hary Soedarto Harjono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to develop a web-based cyber counseling model for guidance and counseling services at SMA Negeri 1 Bayung Lencir. This research is a development study or Research and Development (R&D) using the Borg and Gall development model. The subjects of this research are 11th-grade students of SMA Negeri 1 Bayung Lencir for the 2024/2025 academic year. The research results indicate that 44% of the students expressed a need to utilize e-counseling media, preferring a website as the service medium. Based on the research results, the product feasibility test by material experts showed a score of 88%, categorized as highly feasible, and by media experts, a score of 98.6%, also categorized as highly feasible. Furthermore, the product feasibility test based on student responses showed a score of 94.4%, categorized as highly feasible, and the guidance counselor responses showed a score of 90%, categorized as highly feasible.